Frommovo pojmovanje religije - Šumiga, Dražen (Monitor ISH, 2005)
Fromm's concept of religion. The article addresses the issues of religion, ethics, and humanism in the works of Erich Fromm. It explores the relation between religion and humanism instrumental in constructing the concepts of God, man, and the world as three categories of traditional metaphysics. Concentrating on Fromm's concept of alienation, it also touches on the relation between psychoanalysis and religion, attempting to show that, at least from the humanist vantage point that man is the primary category, there is no antagonism between the two.
Keywords: Fromm, Erich, 1900-1980; religija; religion; psihoanaliza; humanism; humanizem; ethics; etika